Investigating the Mediating role of quality of family life in relationship between parenting stress and children’s behavioral problems - mohamad sajjad Seydi; Khadijeh rezaee; Setareh Hoseini Shurabeh (مطالعات روانشناسی تربیتی, 2019)
Current study aims to Investigating the mediating role of quality of family life in relationship between parenting stress and children’s behavioral problems. Statistical population of this study were all parents of female elementary school students in Kermanshah city in the year 95-94, Among them 500 parents of students  by Multi-step cluster random method were selected. The participants answered the questions of Rotter’s behavioral problems(RBP), parenting stress index-short form (PSI-SF), and family quality of life (FQOL). The data were analyzed by structural equation modeling method using Amos software version 21. Results showed a positive and meaningful relationship (p<0.01, r=0.42) between parenting stress and children’s behavioral problems. Furthermore, relationships between parenting stress and family quality of life (p<0.01, r=-0.47), and family quality of life and children’s behavioral problems were negative and meaningful (p<0.01, r=-0.15). It was also confirmed that mediating role of family quality of life in relation between parental stress and child behavioral problems. Therefore, by improving the quality of family life, moderating the effect of parental stress on the behavioral problems of children. In addition, the implementation of stress management strategies in parents can somewhat prevent the occurrence of children's behavior problems.